A comparative study on cutaneous temperature difference between body and foot among patients of diabetic neuropathy and normal individuals - Sudhir Kumar ,; Albail Singh Yadav,; Nikhil Mishra, (Asian Journal of Medical Sciences, 2024)
Background: As diabetic neuropathy progresses, the pain subsides and eventually disappears, but a sensory deficit persists and a motor deficit may develop. Loss of protective sensation and distal sensory polyneuropathy are major risk factors for foot ulceration and falls due to small and large nerve fiber dysfunction, which predispose to lower extremity amputation. Aims and Objectives: We did a comparative study on the cutaneous temperature difference between the body and foot among patients of diabetic neuropathy and patients of diabetes without neuropathy to establish the role of pedal temperature monitoring in preventing complications of diabetic neuropathy. Materials and Methods: The study was done at Maharani Laxmi Bal Medical College, Jhansi, between April 2021 and November 2022, including two groups of patients (Group A: 100 patients with diabetes without neuropathy and Group B: 100 patients with diabetes as well as with neuropathy). Results: In our study, in group A (diabetic patients without neuropathy), 9% were in 18–30 years, 14% in 31–40 years, 19% in 41–50, 29% in 51–60, and 29% in >60 years. In group B (diabetic patients with neuropathy), 2% were in 31–40 years, 16% in 41–50, 35% in 51–60, and in 46% in >60 years. In our study, the mean foot temperature in group A (diabetic without neuropathy) was 97.35±0.625 and in group B (diabetic patients with neuropathy) was 99.19±1.375. There was a significant difference between the groups on the basis of mean changes in foot temperature (P≥0.01). Conclusion: Based on the above study, we came to the conclusion that foot temperature is significantly higher in diabetic patients with neuropathy. An infrared thermometer can be used as a home-based tool as well as in an outpatient department setting to avoid the dreaded complications of diabetic neuropathy or at least to delay the progression of the same.